Testing Gassmann fluid substitution in carbonates: sonic log versus ultrasonic core measurements - De Paula, Osni; Pervukhina, M.; Gurevich, Boris (SEG, 2010)
The technique of fluid substitution is widely used to model elastic properties of rocks saturated with different fluids The applicability of this technique to in-situ seismic and sonic measurements is a matter of frequent debate. Most of the analysis is based on laboratory measurements, with little or no constraints from field environments. In addition, until recently, most of the data were from sand reservoirs. Applicability of Gassmann fluid substitution to carbonates is even more uncertain. To analyze this problem, we compare elastic moduli obtained using fluid substitution against the moduli obtained from sonic and density logs The dry moduli for fluid substitution are obtained from ultrasonic measurements on 50 core samples from a cretaceous reservoir buried at 5000 meters depth in Santos Basin, offshore Brazil. The good agreement between the saturated moduli obtained from cores and logs is obtained. This shows that the Gassmann equations can be applied not only in siliciclastic reservoirs, but also deep and complex carbonates reservoirs.